Skrb v zdravstveni negi ali zdravstvena nega v (o)skrbi - Klemenc, Darinka (Obzornik zdravstvene nege, 2003)
In our changing times health and social care are of vital importance for comprehensive treatment of individuals and groups. Aging of the population andreducing resources for health, as well as social care of healthy and sick requires a rational attitude to maintaining healthy life style of the population. The article deals with care as the basis of health care centering around a holistic concept of the individual, together with his/her choice of life style, ethic values and good practice, represented also by the carriers of the profession, i.e. nurses, nursing technicians, midwives and nursing aides. Indicated is the need for the combination of health and social care so that they will be acting in unison for the same goals-happy individual, familyand community.
Keywords: Domača oskrba, agencije; Ethics, Nursing; Etika zdravstvene nege; Home Care Agencies; Nursing Care; Social Security; Social Work; Socialno delo; Socialno zavarovanje; Zdravstvena nega